Chromosome-Level Assemblies for the Pine Pitch Canker Pathogen Fusarium circinatum - Lieschen De Vos; Magriet A. van der Nest; Quentin C. Santana; Stephanie van Wyk; Kyle S. Leeuwendaal; Brenda D. Wingfield; Emma T. Steenkamp (Pathogens, 2024)
The pine pitch canker pathogen, Fusarium circinatum, is globally regarded as one of the most important threats to commercial pine-based forestry. Although genome sequences of this fungus are available, these remain highly fragmented or structurally ill-defined. Our overall goal was to provide high-quality assemblies for two notable strains of F. circinatum, and to characterize these in terms of coding content, repetitiveness and the position of telomeres and centromeres. For this purpose, we used Oxford Nanopore Technologies MinION long-read sequences, as well as Illumina short sequence reads. By leveraging the genomic synteny inherent to F. circinatum and its close relatives, these sequence reads were assembled to chromosome level, where contiguous sequences mostly spanned from telomere to telomere. Comparative analyses unveiled remarkable variability in the twelfth and smallest chromosome, which is known to be dispensable. It presented a striking length polymorphism, with one strain lacking substantial portions from the chromosome’s distal and proximal regions. These regions, characterized by a lower gene density, G+C content and an increased prevalence of repetitive elements, contrast starkly with the syntenic segments of the chromosome, as well as with the core chromosomes. We propose that these unusual regions might have arisen or expanded due to the presence of transposable elements. A comparison of the overall chromosome structure revealed that centromeric elements often underpin intrachromosomal differences between F. circinatum strains, especially at chromosomal breakpoints. This suggests a potential role for centromeres in shaping the chromosomal architecture of F. circinatum and its relatives. The publicly available genome data generated here, together with the detailed metadata provided, represent essential resources for future studies of this important plant pathogen.